2017
DOI: 10.1002/eji.201747121
|View full text |Cite
|
Sign up to set email alerts
|

AhR activation increases IL‐2 production by alloreactive CD4+ T cells initiating the differentiation of mucosal‐homing Tim3+Lag3+ Tr1 cells

Abstract: Activation of the aryl hydrocarbon receptor (AhR) by immunosuppressive ligands promotes the development of regulatory T (Treg) cells. Although AhR-induced Foxp3+ Treg cells have been well studied, much less is known about the development and fate of AhR-induced Type 1 Treg (AhR-Tr1) cells. In the current study, we identified the unique transcriptional and functional changes in murine CD4+ T cells that accompany the differentiation of AhR-Tr1 cells during the CD4+ T-cell-dependent phase of an allospecific cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 55 publications
3
31
0
1
Order By: Relevance
“…Higher VZV-Treg and gE-Tcheck percentages at PMR in HZ/ su compared with ZV recipients are also probably related to the higher memory responses in HZ/su. Tregs and Tcheck may play a role in Th1 differentiation by directing the immune response from effector to memory (30)(31)(32). Alternatively, they may signal that Teff cells are being quenched.…”
Section: Resultsmentioning
confidence: 99%
“…Higher VZV-Treg and gE-Tcheck percentages at PMR in HZ/ su compared with ZV recipients are also probably related to the higher memory responses in HZ/su. Tregs and Tcheck may play a role in Th1 differentiation by directing the immune response from effector to memory (30)(31)(32). Alternatively, they may signal that Teff cells are being quenched.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that AhR activation by immunosuppressive ligands promotes the development of Foxp3 + Treg cells (33). However, much is unknown concerning the development of AhR-induced Tr1 cells (34). One study showed that Tr1 but not Foxp3 + Treg cells suppress immune activation via an IL-10-dependent mechanism (35).…”
Section: Discussionmentioning
confidence: 99%
“…AhR also promotes HIF1-α degradation and takes control of Tr1 cell metabolism [ 92 ]. In addition, AhR activation can also initiate the differentiation of mucosal-homing Tim3 + Lag3 + Tr1 cells [ 107 ]. Thus, Trp metabolites promote the differentiation and function of not only Treg cells but also other regulatory T cells, such as Tr1 cells.…”
Section: Regulation Of Trp Metabolites From Gut Microbiota In the Imm...mentioning
confidence: 99%